Methods and Values of Prophet Ibrahim’s Child Education in The Qur’an Surah aṣ-Ṣāffāt Verses 85-113 - Amrin Amrin; Adi Priyono; Nurrahmaniah Nurrahmaniah; Supriyanto Supriyanto (Jurnal Studi Al-Qur'an, 2023)
The impact of globalization causes various kinds of negative behavior and actions in early childhood, causing a degradation of morality and religiosity. The research objective was to determine the concept of Islamic education and the methods and values developed by the Prophet Ibrahim in the education of children in QS aṣ-Ṣāffāt verses 85-113. This study uses a linguistic (philological/semantic) approach regarding the verses of the al-Qur'an Surah Aṣ-Ṣāffāt Verses 85-113, with the type of library research. The primary source in this research is the al-Qur'an surah aṣ-Ṣāffāt verses 85-113, and the secondary sources include the interpretation books, such as: "Tafsir Al-Azhār", Buya Hamka, Tafsir Al-Mishbāh, Quraish Shihab, Al-Qur’an and its Tafseer, and others. The data collection technique uses a library research technique. With the data collection method using documentation method using content analysis (content analysis).The results of the research show that the methods used by Prophet Ibrahim in surah ash-Shaffat verses 85-113 in children education include the tazkiyah method (purification), the method of choosing the environment, the method of having a vision, mission and goals, communication methods, methods of building a spirit of sacrifice to obtain pleasure, love and help of Allah Most High and methods of giving gifts (reward). The values developed by Prophet Ibrahim in surah ash-Shaffat verses 85-113 in children's education include the value of faith, the value of praying, the value of democratic attitudes, the value of patience, the value of tawakal (surrender) and the value of humanization. The concept of Islamic education as a process of a series of activities to humanize humans (humanization), or efforts to help humans to be able to manifest themselves according to their human dignity, based on divine messages with an attitude and personality totality surrendering to Him in all aspects of life to seek pleasure his.